EFEKTIVITAS BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PENYESUAIAN SOSIAL PANTI ASUHAN AISYIYAH KOTA PARIAMAN - Wista Rahayu; Syawaluddin; Nuraliman (CV. ADIBA ASIHA AMIRA, 2023)
This research begins with a phenomenon that occurs in foster children who experience social and personal problems, such as foster children who do not like criticism from other people, do not understand social ethics and participate less in social situations and even prefer to be alone. The aim of this research is to determine the effectiveness of group guidance services in improving the social adjustment of the Aisyiyah Orphanage Foundation in Pariaman City. This research uses a quantitative approach with pre-experiment method, one group pre-test and post-test. Samples used in This research was 8 students. The instrument used in this research is a scale measurement, namely a scale developed to measure the social adjustment of foster children. The data analysis technique uses the Wiloxon Rank Test. The results obtained inThis research is a pre-test score with a total score of 259 and a post-test score with a total score 531, after the scale was introduced and the results were very effective because the hypothesis was accepted shows the Aaymp.sig value of 0.012, less than 0.05, so there is a difference in scores before and after implementing group guidance services to improve the social adjustment of foster children at the Aisyiyah orphanage in Pariaman City.